Biochemical and molecular predictors for prognosis in nonketotic hyperglycinemia. Issue 4 (10th August 2015) - Swanson, Michael A.; Coughlin, Curtis R.; Scharer, Gunter H.; Szerlong, Heather J.; Bjoraker, Kendra J.; Spector, Elaine B.; Creadon‐Swindell, Geralyn; Mahieu, Vincent; Matthijs, Gert; Hennermann, Julia B.; Applegarth, Derek A.; Toone, Jennifer R.; et al.
<x xml:space="preserve">Abstract</x> Objective Nonketotic hyperglycinemia is a neurometabolic disorder characterized by intellectual disability, seizures, and spasticity. Patients with attenuated nonketotic hyperglycinemia make variable developmental progress. Predictive factors have not been systematically assessed. Methods We reviewed 124 patients stratified by developmental outcome for biochemical and molecular predictive factors. Missense mutations were expressed to quantify residual activity using a new assay. Results Patients with severe nonketotic hyperglycinemia required multiple anticonvulsants, whereas patients with developmental quotient (DQ) > 30 did not require anticonvulsants. Brain malformations occurred mainly in patients with severe nonketotic hyperglycinemia (71%) but rarely in patients with attenuated nonketotic hyperglycinemia (7.5%). Neonatal presentation did not correlate with outcome, but age at onset ≥ 4 months was associated with attenuated nonketotic hyperglycinemia. Cerebrospinal fluid (CSF) glycine levels and CSF:plasma glycine ratio correlated inversely with DQ; CSF glycine > 230 μM indicated severe outcome and CSF:plasma glycine ratio ≤ 0.08 predicted attenuated outcome. The glycine index correlated strongly with outcome. Molecular analysis identified 99% of mutant alleles, including 96 novel mutations. Mutations near the active cleft of the P‐protein maintained stable protein levels. Presence of 1 mutation with residual activity was necessary but not sufficient for attenuated outcome; 2 such mutations conferred best outcome. Divergent outcomes for the same genotype indicate a contribution of other genetic or nongenetic factors. Interpretation Accurate prediction of outcome is possible in most patients. A combination of 4 factors available neonatally predicted 78% of severe and 49% of attenuated patients, and a score based on mutation severity predicted outcome with 70% sensitivity and 97% specificity. Ann Neurol 2015;78:606–618